Emerging issues in information technology. - REICHMAN, Jerome (1996)
Describes the general problem that has challenged world intellectual property law. Discusses the intellectual property rights that states may claim in their own publications, and how that might affect the practice of international law and the scholarship of international law over the next decade or so. Looks at some of the factors that the international community will have to deal with as it tries to structure an acceptable standard for the protection of technology.